Dystanse wobec odmieności w doświadczeniu Polaków czasu zmiany - Grotowska, Stella (Wydawnictwo Uniwersytetu w Białymstoku, 2004)
The paper considers the problem of cultural diversity appearing in an everyday experience of Polish society during the period of political and economic transformations after 1989. The research is based on anonymous, little-structured interviews completed in Wroclaw in 2002. The analysis of the statements contained therein revealed two ways of articulation of differences: in terms of nationality and interms of individualization. In the first case the dissimilarities are perceived negatively, in the second – are described as “insignificant”, accidental, individual. Both strategies are used to invalidate or overcome the differences.
Keywords: cultural differences; cultural otherness; social distance; strangeness; Polish tranformation